The Colleration Between Vocabulary Mastery And The Ability To Arranged Jumlah Ismiyah At MIS Hikmatul Husna - Siti Aisyah; Muhammad Qadhafi; Azmy Ali Muchtar (Universitas Al-Amien Prenduan, 2026)
Abstract This study aims to analyse the relationship between vocabulary proficiency and the ability to construct a noun phrase among fifth grade students at the Al-Hikma AlHasna Islamic Primary School, in light of the importance of Arabic in developing basic language skills among learners. The study used the quantitative approach of the correlational descriptive design with a cross-sectional design, where data were collected in a single time period without any intervention in the variables. The study included all 26 students in the community, using a comprehensive approach to ensure accurate and comprehensive data. The data were collected using three main tools: tests to measure the level of vocabulary proficiency and the ability to form a noun phrase, as well as interviews and observations to support the quantitative data and interpret the results more deeply. The data were analysed using Pearson's product-moment correlation coefficient to determine the strength and direction of the relationship between the two variables. The results showed that the average level of vocabulary proficiency among the students was 93.27, which is excellent, while the average level of ability to construct a noun phrase was 84.46, which is very good. The statistical analysis also showed that the value of the correlation coefficient (Rxy = 0.516) indicates a moderate and statistically significant relationship between the two variables. The calculated value of r exceeded the tabulated values at significance levels of 5% and 1%, indicating acceptance of the alternative hypothesis and rejection of the null hypothesis. As R² = 0.266, it was found that vocabulary proficiency explains approximately 26.6% of the variation in the ability to construct a noun phrase, while the remaining percentage is due to other factors such as proficiency in grammar and frequent language practice in the educational context. The study concludes that mastery of vocabulary contributes positively to the ability of pupils to build a noun phrase correctly, emphasising the importance of integrating vocabulary teaching with language applications in classroom activities to improve language proficiency among primary school students. Keywords: language arabic, teaching, vocabulary, jumlah ismiyyah.